Analisis Yuridis Putusan Pengadilan Negeri Mataram Nomor 3/Pdt.G/2021/Pn Tentang Keabsahan Peralihan Hak Atas Tanah - Farah Sahirah; H. Arba Arba; Wiwiek Wahyuningsih (Private Law, 2023)
This research aims are to know the validity of unregistered sale and purchase agreement with the Title Certificate. Type of this research was normative legal research which applied conceptual, statute and case approaches. The used legal analysis of this study was legal interpretation. Result of this study shows that legal force in the verdict Number 3/PDT.G/2021/PN is valid and has legal force since there was witness statement in the court. The panel of Judges gave permission or power of attorney to the Plaintiff for and on behalf of the Defendant before the authorized Land Deed Making Officer (PPAT) to sign the Deed of Sale and Purchase/Transition of land rights with the ownership certificate. The transfer of land rights does not occur, while the agreement remains valid and has the same binding legal force as an authentic deed. It is better if every agreement is made by and before a Notary.